Engineering death resistance in CHO cells for improved perfusion culture. Issue 1 (31st December 2022) - MacDonald, Michael A.; Nöbel, Matthias; Martínez, Verónica S.; Baker, Kym; Shave, Evan; Gray, Peter P.; Mahler, Stephen; Munro, Trent; Nielsen, Lars K.; Marcellin, Esteban
ABSTRACT: The reliable and cost-efficient manufacturing of monoclonal antibodies (mAbs) is essential to fulfil their ever-growing demand. Cell death in bioreactors reduces productivity and product quality, and is largely attributed to apoptosis. In perfusion bioreactors, this leads to the necessity of a bleed stream, which negatively affects the overall process economy. To combat this limitation, death-resistant Chinese hamster ovary cell lines were developed by simultaneously knocking out the apoptosis effector proteins Bak1, Bax, and Bok with CRISPR technology. These cell lines were cultured in fed-batch and perfusion bioreactors and compared to an unmodified control cell line. In fed-batch, the death-resistant cell lines showed higher cell densities and longer culture durations, lasting nearly a month under standard culture conditions. In perfusion, the death-resistant cell lines showed slower drops in viability and displayed an arrest in cell division after which cell size increased instead. Pertinently, the death-resistant cell lines demonstrated the ability to be cultured for several weeks without bleed, and achieved similar volumetric productivities at lower cell densities than that of the control cell line. Perfusion culture reduced fragmentation of the mAb produced, and the death-resistant cell lines showed increased glycosylation in the light chain in both bioreactor modes. These data demonstrate that rationally engineered death-resistant cell lines are ideal for mAb production in perfusion culture, negating the need to bleed the bioreactor whilst maintaining product quantity and quality.